Implementasi personalized learning berbasis pembelajaran berdiferensiasi untuk meningkatkan minat belajar siswa dalam pembelajaran matematika - Ayu Fitria Dwi Nuraini; Lisanul Uswah Sadieda; Sarmatun (Papanda Journal of Mathematics and Science Research, 2026)
This study aims to implement personalized learning based on differentiated learning in order to increase the interest in learning mathematics of class X-6 students of SMA Negeri 15 Surabaya. The research method used is quantitative with a quasi-experimental design of the One Group Pretest-Posttest type. The research subjects were 30 students who participated in learning using LKPD adapted to their learning zones (visual, verbal, and practical). The research instrument was a learning interest questionnaire given before and after treatment. Data analysis was carried out through normality tests, t-tests, and N-Gain calculations. The results showed that the pretest and posttest data were normally distributed and there were significant differences between the two (Sig. 0.000 < 0.05; |t count| 8.111 > t table 2.002). The average N-Gain obtained was 0.51 with a medium category, with a distribution of achievements of 30% high, 50% medium, 16.7% low, and 3.3% unchanged. These findings indicate that the implementation of personalized learning based on differentiated learning is able to increase students' interest in learning through learning that is more personal, relevant, and in accordance with individual learning styles. This research also has a positive impact on mathematics learning, namely creating a more adaptive learning environment, increasing active student involvement, reducing negative perceptions of mathematics, and helping students understand concepts more deeply through learning paths that suit their readiness and preferences.